ChemInform Abstract: Electrophilic ipso‐Iodocyclization of N‐Benzyl‐N‐(1‐naphthyl)propiolamides: Synthesis of Complex Polycyclic Lactams. Issue 27 (8th July 2014) - Wang, Li‐Jing; Zhu, Hai‐Tao; Qiu, Yi‐Feng; Liu, Xue‐Yuan; Liang, Yong‐Min
Abstract The first protocol involving a Friedel—Crafts‐type reaction combined with an intramolecular electrophilic ipso‐iodocyclization of title propiol amides is developed.